The journey from precontemplation to action: Transitioning between electronic medical record systems. Issue 1 (January 2016) - Bentley, Thomas; Rizer, Milisa; McAlearney, Ann Scheck; Mekhjian, Hagop; Siedler, Monica; Sharp, Karen; Teater, Phyllis; Huerta, Timothy
Abstract : Background: Health care organizations, in response to federal programs, have sought to identify electronic medical record (EMR) strategies that align well with their visions for success. Little exists in the literature discussing the transition from one EMR strategy to another. Purpose: The analysis and planning process used by a major academic medical center in its journey to adopt a new strategy was described in this study. We use the transtheoretical model of change to frame the five phases through which the organization transitioned from a best-of-breed system to an enterprise system. Methodology/Approach: We explore the five phases of change from the perspective of a maturing approach to new technology adoption. Data collection included archival retrieval and review as well as interviews with key stakeholders. Findings: Although there was always a focus on some enterprise capabilities such as computerized physician order entry, the emphasis on EMR selection tended to be driven by specialty requirements. Focusing on the patient across the continuum of care, as opposed to focusing on excessive requirements by clinical specialties, was essential in forming and deploying a vision for the new EMR. Practice Implications: This research outlines a successful pathway used by an organization that had invested heavily in EMR technology and was faced with evaluating whether to continue that investment or start with a new platform. Rather than focusing on the technology alone, efforts to reframe the discussion to one that focused on the patient resulted in less resistance to change.